Analytical Nominations Structural-Semantic Features in the Engineering Technology Field - Lilia, Lilia; Derevyanko, Ludmyla; Mizina, Olha (International Journal of Engineering and Technology, 2018)
Nominating special concepts method by means of analytical terminology belongs to the most active and most productive in the field of engineering technologies, taking into account the specificity of scientific knowledge, which is constantly expanding and replenishing. Analytical terms are subject to internal language laws and general-language influences, reflecting the general tendencies in modern Ukrainian literary language development. Analytical terms by structure type are divided into simple and complex. The highest productivity is marked by two-part analytical terms. In the analyzed constructions, the onomassiological basis is a nuclear component expressed by a noun in the nominal case. Onomasiological sign specifies and detailies the nuclear component meaning. Terminological constructions, having three or more components, are formed by expanding and specifying base component values. Analytic term grammatical and semantic structures are closely interrelated. Terminology unit semantic unity degree depends on the presence or absence of words that are not scientific and technical terms in its composition. Semantic unity increases if one or more analytic term components are formed by narrowing their meaning, metaphorical or metonymic rethinking of non-special words.Â